Persistence and drop-out of distance learners in Sub-Saharan Francophone Africa: Cases of Togo - (:unkn) unknown (My University, 2016)
To address the problems facing sub-Saharan educational systems, recourse is often made to Distance Learning. The Distance Learning programs implemented in French-speaking Sub-Saharan Africa (FSSA) are characterized by a high rate of learners learning activities leading to an end. This contrasts with the high rate of dropout usually identified in this training mode. It is the effectiveness of distance learning devices affecting FSSA that interests us in this study which aimed to understand the practices of educational engineering implemented to foster the persistence of learners.To achieve this goal, we have mobilized Kember (1989) model as the theoretical framework of a qualitative/interpretative approach using the multiple cases study method. Twenty-one (21) students resident in Togo at the time of their learning, 17 persevering and 4 dropouts, intentionally selected in three devices were interviewed. We also operate with documents presenting and/or analyzing such devices. This literature review was supplemented by interviews with supervisors to get a better understanding of the operation of said devices.From the analysis of the data collected, it appears that the persistence and the dropout of learners result from the interactions of several factors that can be grouped into three categories. These are the individual characteristics of the learner including his motivation for the training, factors related to his socio-professional environment and the factors related to the training offer. The interactions of these three categories of factors are such that it is difficult or ineffective to isolate the impact of a singularamong them on the decision of the learner to persevere or dropout. Four practices of educational engineering which are: the positioning of the training; selection at entry; learner progress in cohort and human interactions were identified as strategies used by distance learning programs affecting FSSA to foster the persistence of lea
Keywords: African Research